2009
DOI: 10.1002/eji.200838418
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal exposure to staphylococcal superantigen improves induction of oral tolerance in a mouse model of airway allergy

Abstract: The hygiene hypothesis suggests that lack of microbial stimulation in early infancy may lead to allergy, but it has been difficult to identify particular protective microbial exposures. We have observed that infants colonised in the first week(s) of life with Staphylococcus aureus have lower risk of developing food allergy. As many S. aureus strains produce superantigens with T-cell stimulating properties, we here investigate whether neonatal mucosal exposure to superantigen could influence the capacity to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 45 publications
(56 reference statements)
3
17
0
1
Order By: Relevance
“…[137][138][139] There are few experimental studies concerned with whether and how microbiota influences the development of allergy. 140 We have addressed the question of whether the intestinal microbiota affects the induction of mucosal (oral) tolerance against the birch pollen allergen. The Bet v1 allergen was applied intranasally or intragastrically in an experimental model of allergy induced by subcutaneous sensitization with the same allergen, and induction of tolerance was tested after application of an inducing allergen dose.…”
Section: Allergymentioning
confidence: 99%
“…[137][138][139] There are few experimental studies concerned with whether and how microbiota influences the development of allergy. 140 We have addressed the question of whether the intestinal microbiota affects the induction of mucosal (oral) tolerance against the birch pollen allergen. The Bet v1 allergen was applied intranasally or intragastrically in an experimental model of allergy induced by subcutaneous sensitization with the same allergen, and induction of tolerance was tested after application of an inducing allergen dose.…”
Section: Allergymentioning
confidence: 99%
“…In the analogous system of Ag high dose tolerance in a Th2-type response described above, treatment of recipient mice before sensitization with intestinal epithelial cell-derived tolerosomes found in serum of mice orally tolerized to OVA [160] induced oral tolerance. Further, as a possible example of a relationship between bacterial mEV and asthma tolerance, neonatal exposure to the enterotoxin superantigen of Staphylococcus aureus augmented subsequent induction of oral tolerance to OVA in a mouse model of asthma [161]. In contrast, exosomes from an epithelial cell line cultured in the presence of an OVA hydrolysate of peptides with IFNγ were not tolerogenic, but instead activated the humoral Ab immune response to OVA [162].…”
Section: Exosomes In Immune Tolerance and Suppression Of Asthmamentioning
confidence: 99%
“…Thus, deletion and autonomous anergy are natural mechanisms that prevent hyper-responsiveness of T cells to S. aureus enterotoxins. An excellent clinical role for these pathways was recently revealed in a model of OVA-induced airway allergy [53]. The authors demonstrated that SEA pre-treatment in neonates enhanced OVA oral tolerance, which conferred protection against intranasal OVA challenge when the mice enter adulthood.…”
Section: How Se Affects Immune T Cell Tolerancementioning
confidence: 99%